Afrontamiento del estrés generado durante el internado rotativo en estudiantes de Medicina de la Universidad Nacional de Loja. - Granda Orosco, Leydi Elizabeth (2024)
Stress is a systemic imbalance between work demands or requirements and the capacity to respond to situations perceived as stressful. One of the population groups most affected by this pathology is health personnel and students. This study aims to determine the strategies used to cope with stress by rotating interns of the Medicine career of the National University of Loja during the period from October 2022 to March 2023. A total of 103 Medicine interns participated in this quantitative, descriptive, crosssectional cohort research. A survey was used for sociodemographic characterization, the Work Stress Test adapted from the Psychosomatic Problems Questionnaire (CPP) to determine the level of stress and the Coping with Stress Questionnaire (CAE) to identify the stress coping techniques they used. It is relevant to understand the sociodemographic reality of the inmates to understand who they are, how stressed they are and what they are doing to cope with stress, in this study we obtained a young population in which a large part are aged between 20-24 years 58, 5 % (n=60), the majority were women 68.93% (n=71), from the province of Loja 81.55% (n=84), 93.20% (n=96) were single, 84.47% (n=87) professed Catholicism and 41.45% (n=43) lived with their parents and siblings before starting the internship. In addition, most of them did not report any personal pathological history 86.41% (n=89). The boarding school students present stress, and according to the applied test, 55.34% (n=57) are in the mild stress level. Regarding coping techniques, 82.5% (n=85) were considerably inclined to only one coping technique. The most frequently used technique was problem-solving focus (PSF) with 50.49% (n=52), this being a healthy, positive and proactive dimension of coping. On the other hand, it was evidenced that less proactive and passive techniques, such as avoidance (EV) and negative self-focusing (AFN), were not widely accepted